Motivated Procrastination - Charlotte Cordes; Jana Friedrichsen; Simeon Schudy (Center for Economic Studies and ifo Institute (CESifo), 2024)
Procrastination is often attributed to time-inconsistent preferences but may also arise when individuals derive anticipatory utility from holding optimistic beliefs about their future effort costs. This study provides a rigorous empirical test for this notion of 'motivated procrastination'. In a longitudinal experiment over four weeks, individuals must complete a cumbersome task of unknown length. We find that exogenous variation in scope for motivated reasoning results in optimistic beliefs among workers, which causally increase the deferral of work to the future. The roots for biased beliefs stem from motivated memory, such that procrastination may persist even if uncertainty is eventually resolved.
Keywords: C91; D83; D84; D90; D91; 330; anticipatory utility; beliefs; memory; motivated cognition; procrastination; real effort; task allocation